TYPOLOGY OF PROSE OF MARKO VOVCHOK AND TONI MORRISON: PROBLEMATICS, CHARACTERS - Iermak, L. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In this article we survey social, psychological and gender problematics in the fiction of Marko Vovchok and Toni Morrison on the comparative level. We try to determine level of actualization of the author’s socio-psychological and gender believes of Marko Vovchok as shown in miscellany «Folk Stories», story «College Girl» and «Three fates». We analyze a problem of a tragic situation of a complete loss of personal and ethnic identity of Afro-American people as well as the problem of socialization of black women in the 20th-30th of XX th century, as shown in such works of Toni Morrison as "Beloved," "Song of Solomon" and "Sula".